Associations between rs3480 and rs16835198 gene polymorphisms of FNDC5 with type 2 diabetes mellitus susceptibility: a meta-analysis - Yang, Xianqin; Ni, Li; Sun, Junyu; Yuan, Xiaolu; Li, Dezhong (Frontiers in Endocrinology, 2022)
Background FNDC5 is a novel and important player in energy regulation related to glucose metabolism and insulin levels. Thus, it may affect the incidence of type 2 diabetes mellitus (T2DM). Nevertheless, the association between FNDC5 single nucleotide polymorphisms (SNPs) and susceptibility to T2DM remains unclear. The aim of this meta-analysis was to explore whether the SNPs, rs3480 and rs16835198, are associated with the risk of T2DM. Methods Studies published before February 1st, 2022 were screened to identify the included studies. R software was also applied for calculation of odds ratio (OR), 95% confidence interval (95% CI), heterogeneity, and sensitivity analysis. Results Seven studies for rs3480 (involving 5475 patients with T2DM and 4855 healthy controls) and five studies for rs16835198 (involving 4217 patients with T2DM and 4019 healthy controls) were included in this meta-analysis. The results revealed a statistically significant association of rs3480 with T2DM under homozygote (GG vs AA: OR = 1.76, 95% CI = 1.31–2.37, P = 0.0002, I2 = 59%) genetic model. However, there was no statistically significant correlation between rs16835198 and susceptibility to T2DM under allelic (G vs T: OR = 1.33, 95% CI = 0.94–1.89, P = 0.11, I2 = 84%), heterozygote (GT vs TT: OR = 1.17, 95% CI = 0.80–1.69, P = 0.42, I2 = 71%), homozygote (GG vs TT: OR = 1.35, 95% CI = 0.95–1.94, P = 0.10, I2 = 62%), recessive (GG+GT vs TT: OR = 1.25, 95% CI = 0.88–1.79, P = 0.22, I2 = 72%), and dominant (GG vs GT+GG: OR = 1.20, 95% CI = 0.96–1.50, P = 0.11, I2 = 46%) genetic models. Conclusions The present meta-analysis revealed that rs3480 in FNDC5 is significantly associated with susceptibility to T2DM, while rs16835198 does not show such an association.